PENGARUH KRISIS EKONOMI GLOBAL TERHADAP EKONOMI DI INDONESIA - TITA DEITIANA (Media Bisnis, 2014)
Efforts to combat the global economic crisis of the nation Indonesia should be more careful in accepting foreign products coming into the country, especially during this time more people favor foreign products this does not add to the economy in Indonesia, but the economic down turn. Indonesia's dependence on International Monetary Fund debt problems and make more and more difficult to cover other debts. The Indonesian people pay more attention to small businesses that exist in order to be able to decrease unemployment.